(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The problems and prospects for implementing the “University 3.0” concept in domestic higher education are considered. Experience in implementing the concept of “University 3.0” in universities of the republic occurs mainly according to the models of developed countries, taking into account the existing system of higher education in Uzbekistan.